Atrial fibrillation due to oral methylprednisolone in a patient with membranoproliferative glomerulonephritis. - Dogukan, Ayhan; Ilkay, Erdogan; Poyrazoglu, Orhan K; Gunal, Ali Ihsan; Ozgen, Metin; Pekdemir, Murat (My University, 2008)
Cardiac adverse effects of intravenous pulse methylprednisolone administration are well known, but there is little information about the cardiac side effects of oral methylprednisolone in the literature. We present a 41 year-old man with membranoproliferative glomerulonephritis in whom developed atrial fibrillation after oral methylprednisolone therapy.
Keywords: Administration, Oral; Adult; Atrial Fibrillation; Glomerulonephritis, Membranoproliferative; Glucocorticoids; Humans; Male; Methylprednisolone; glucocorticoid; methylprednisolone; adult; article; case report; chemically induced disorder; heart atrium fibrillation; human; male; membranoproliferative glomerulonephritis; oral drug administration